2007
DOI: 10.1007/s00726-007-0563-7
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the human proteome for non-redundant peptide islands

Abstract: We describe immune-proteome structures using libraries of protein fragments that define a structural immunological alphabet. We propose and validate such an alphabet as i) composed of letters of five consecutive amino acids, pentapeptide units being sufficient minimal antigenic determinants in a protein, and ii) characterized by low-similarity to human proteins, so representing structures unknown to the host and potentially able to evoke an immune response. In this context, we have thoroughly sifted through th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…On the whole, the human proteome consists of ∼2.4 million of pentapeptides, about half million of which occur only once, whilst the remaining ones repeatedly recur in the human proteins even hundreds of times. Including multiple occurrences, the human proteome consists of ∼16 million pentapeptides [32].…”
Section: The Weakness Of the Primary Electrostatic Interaction: Pentamentioning
confidence: 99%
“…On the whole, the human proteome consists of ∼2.4 million of pentapeptides, about half million of which occur only once, whilst the remaining ones repeatedly recur in the human proteins even hundreds of times. Including multiple occurrences, the human proteome consists of ∼16 million pentapeptides [32].…”
Section: The Weakness Of the Primary Electrostatic Interaction: Pentamentioning
confidence: 99%
“…Our labs are taking advantage of this unique chance for investigating the molecular determinants possibly involved in human susceptibility to infectious agents. [1][2][3] We recently analyzed a set of viral proteomes for sequence similarity to the human proteome, and reported a massive and widespread peptide overlapping between viral and human proteins. 4,5 Here we analyze a set of 20 pathogenic and 20 non-pathogenic bacterial proteomes, and report that all of the bacterial proteomes studied exhibit an unexpectedly high level of peptide sharing with the human proteome, irrespective of the microbe's pathogenicity.…”
Section: Introductionmentioning
confidence: 99%
“…One promising sequence feature, which has recently been suggested as important in disease-related proteins (derived from either pathogens or the host itself ), is the presence of short peptide segments that are found rarely or never in the host proteome. In a broad-based analysis, Capone et al (2008) found that such rare peptide sequences are found unexpectedly often in proteins implicated in autoimmunity and cancer, and Amela et al (2007) discovered that there exists surprisingly little sequence similarity between human proteins and B-cell epitopes derived from pathogens. In a more narrowly defined study, Rolland et al (2007) studied peptides derived from HIV-1, and discovered a negative correlation between similarity to the human proteome and frequency of immune recognition.…”
Section: Introductionmentioning
confidence: 99%